Our Acute Appendicitis Cases in a One Year Period - Çebi, Kibar (Fırat University, 2002)
Aim: The aim of this study was to determine main characteristics and treatment results of patients admitted to our hospital with the preoperative diagnosis of acute appendicitis in a 12 month period. Material and Method: In the present study we retrospectively evaluated a total of 177 cases, who were admitted to our hospital and treated with preoperative diagnosis of acute appendicitis in our hospital between January 2001-December 2001, Results: Of the patients, one hundred and two cases were male while the remaand seventy two were female. In 24 out cases perforated appendicitis was present, and in two cases plastrone was present. Among the 9 cases with post operative complications, wound infection was the leading complication with 5 cases, post operative ileus in 3 cases and intraabdominal abscess in one case was present, respectively. Conclusion: The patients admitted to our hospital with abdominal pain and diagnosed with acute appendicitis in our hospital were rapidly evaluated and treated and the possible post operative complications were minimised.

Amaç: Bu çalışmada, hastanemize 12 ay süresince karın ağrısı şikayeti ile müracaat eden, klinik ve labaratuvar olarak akut apandisit tanısı alan hastaların demografik özellikleri ve tedavi sonuçlarının değerlendirilmesi amaçlanmıştır. Gereç ve Yöntem: Ocak-Aralık 2001 tarihleri arasındaki 12 aylık süre içinde hastanemize karın ağrısı nedeniyle başvurup akut apandisit ön tanısı konarak tedavi edilen 177 olgu retrospektif olarak değerlendirilmiştir. Bulgular: Olguların 102'si erkek 75'i kadın idi. Ameliyat bulgularına göre 11 kadın hastada jinekolojik patoloji saptandı. Olguların 24'ünde perforasyon, 2 olguda plastrone apandisit saptandı. Dokuz olguda gelişen posloperatif komplikasyonların dağılımı; 5 vakada yara enfeksiyonu, 3 olguda post operatif ileus, olguda da intraabdominal apse şeklinde idi. Sonuç: Hastanemize karın ağrısı ile gelen ve akut apandisit tanısı konulan hastalar hızla değerlendirilerek tedavi idilmiş ve oluşabilecek komplikasyonlar en aza indirilmiştir.
BİR YILLIK AKUT APENDİSİT SONUÇLARIMIZ